The Effect of the Guided Inquiry Learning Model on the Critical Thinking Skills of Junior High School Students Class VIII about Vibration, Waves, and Sound - Hidayah Hidayah; Arif Sholahuddin; Maya Istyadji (Program Studi Pendidikan IPA, Universitas Lambung Mangkurat, 2023)
Research has been carried out on the kamislot effect of the guided inquiry learning model on the critical thinking skills of VIII grade junior high school students on the subject of vibrations, waves, and sounds at SMP Negeri 27 Banjarmasin. This study aims to describe the effect of the guided inquiry learning model on the critical thinking skills of eighth-grade junior high school students on the subject of vibration, waves, and sound. The type of research used in this research is the preexperimental method with the experimental design of The One Group Pretest Posttest. The research subjects in this study were conducted using random sampling. The research subjects in this study were class VIII E as many as 33 people in the experimental class. The data collection technique used the test technique. The data analysis technique uses the t-test to analyze the effect of the guided inquiry learning model on students' critical thinking skills. From the results of the t-test, the value of students' critical thinking skills was obtained with sig (0.000) < α = 0.05, meaning that there was a difference between the pretest and posttest results of students' critical thinking skills using the guided inquiry learning model. The research results show that the guided inquiry learning model influences students' critical thinking skills so this learning model can be used as an alternative learning model in schools to improve student's critical thinking skills.